An introduction to the ECB's survey of professional forecasters - Juan Angel Garcia (European Central Bank (ECB), 2003)
This paper provides a detailed overview of the ECB's Survey of Professional Forecasters (SPF), a quarterly survey of euro area key macroeconomic variables conducted by the European Central Bank since 1999. Its purpose is to provide the necessary information for anyone interested in analysing or reporting the survey results. First, its motivations, the panel composition and the structure of the questionnaire are thoroughly explained. The results of the first 18 survey rounds for the three variables covered ? HICP inflation, the real GDP growth rate and the unemployment rate ? for the different horizons are then analysed in detail, including the information content of the uncertainty surrounding those forecast on the basis of the reported probability distributions for each of the variables and horizons. Finally, a comparison to other similar surveys, both for the euro area and the US economy, is also provided.
Keywords: 330